Analysis of Influencing Factors to Increase Product Selling Value During the Covid-19 Pandemic (Case Study of Small and Medium Enterprises (Smes) in Kampung Sejahtera Mandiri Teras Pancasila Tangerang, Banten) - Fx. Pudjo Wibowo; Agus Kusnawan; Eso Hernawan (Fakultas Bisnis, 2022)
Analysis of factors that influence To Increase Product Selling Value During the Covid 19 Pandemic, in this case how much both / individually and jointly between independent variables (price, location, promotion and service) affect the dependent variable (Decision Making Purchasing Products During the Covid 19 Pandemic). This research was carried out by Small and Medium Enterprises (UKM) at Kampung Sejahtera Mandiri Teras Pancasila, Tangerang City, Banten by distributing questionnaires to questions while the research sample was used by simple random sampling . Data collection by field studies (interviews, observations, questionnaires) was shown to small and medium enterprises, small businesses. Medium (UKM) Kampung Sejahtera Mandiri Teras Pancasila in Tangerang City, Banten with a total of 100 SME consumers. Statistical data analysis used reliability, validity, normality, autocorrelation, multicollinearity heteroscedasticity, coefficient determination, individual tests (t-test) and joint tests (f-test), with the SPSS 25 statistical tool. The t shows that the independent variables both have a positive and significant influence on the dependent variable. A case study on Small and Medium Enterprises (UKM), Kampung Sejahtera Mandiri Teras Pancasila, Tangerang City, Banten with the results obtained that the t value of the 2.001 price is > ttable 1 .65 and probability .0048 < 0.05, the t value 1.774 for location is. > ttable 1.65 and . probability 0039 < 0.05, the value of t count promotion is 5.823. > ttable 1.65 and .probability 0000 < 0.05 and the value of t count service is 7.401. > )ttable 1.65 and . probability 0000 < 0.05 The result of F count is 172,359 level significance 0.000 then F count > F table (94,925 > 3,87 significance level 0.000 <0.05, the independent variable simultaneously has a positive and significant influence on the dependent variable in the case study on Small and Medium Enterprises (UKM), Kampung Sejahtera Mandiri Teras Pancasila, Tangerang City, Banten and the value of the coefficient of multiple determination R2 is 87.9, % explained the independent variable factors (price, location, promotion and service) and the remaining 100%-87, 9% = 12.1% the results obtained from other variables are not included from the independent variable.